Caracterização molecular, físico-química de frutos e fenológica do Banco de Germoplasma de cajá-umbú na Zona da Mata de Pernambuco - LIRA JÚNIOR, José Severino de (2005)
Cajá-umbú (Spondias mombin L. x Spondias tuberosa Arr. Cam.) is a native northeast Brazilian fruit tree. He is distinguished for the production of fruits of raised potential nourishing and economic. Despite the ample perspective of commercial exploration, cajá-umbú still meets in wild state. The eminent risks of genetic erosion and extinguishing evidence the necessity of conservation of this genetic resource. This work had as objective variability the identify and genetic similarity coefficients estimate, physical and physical-chemical characterization of fruits and phenological of cajá-umbú of germoplasm bank of the Empresa Pernambucana de Pesquisa Agropecuária-IPA in the Tropical Rainforest Zone of Pernambuco State, aiming at to identify promising materials for future commercial use and in works of genetic improvement. Through the eletroforese technique was analyzed the isozymes esterase (EST), alcohol desidrogenase (ADH), fosfatase acid (the ACP) e peroxidase (POX) extracted of young leafs of the 33 cajá-umbú genotypes. System EST that translated greater isoenzymatic polimorphism and number of polimorphics bands, whose efficiency in the identification of variability between the genotypes, had allowed the grouping in two main groups. During frutification samples of total yellow fruits in 19 cajá-umbú of genotypes was collected, being, immediately, processed the physical determination and physical-chemical. The data were analyzed through the descriptive statistics. Genotypes 6; 8; 10; 12; 14; 17; 19; 21; 22 and 27 are distinguished for presenting weight of fruits above of the average. Genotypes 6; 10;19; 21; 23 and 27 are distinguished for the values of relation SST/ATT above of the standard of identity and quality for cajá. With to the phenologic relation, 12 genotypes during the period of 12 months with comments, biweekly, referring was studied following phenologic: leaf fall (LF), leaf flushing (LFl), flowering (FL) and fruiting (FR).The majority of the genotypes had simultaneously lost its leaf in the month of august, ending of the rainy station. The young leaf emission occurred during all period of evaluation. The budding had beginning in august and lasted until february, and the fruition with beginning in november, was drawn out until may.